INVESTIGATING THE FACTORS AFFECTING STUDENTS’ PROBLEMS IN SPEAKING PERFORMANCE (A CASE STUDY IN ENGLISH EDUCATION DEPARTMENT OF WIRALODRA UNIVERSITY) - Natalia Anggrarini; Atikah Wati; Nurfatma Devi; Suwardi (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Speaking is considered the most challenging skill in language learning, especially in an academic speaking context. It is uncommon for the students to find the problems and need more effort to have a good speaking performance. Therefore, this research aimed to investigate the factors affecting students’ problems in speaking performance. This research investigates performance conditions and affective factors mentioned by Tuan & Mai (2015). This research was attended by 20 students of the 4th semester in the English Education Department of Wiralodra University. The instrument of this research used a questionnaire and interview. Twenty students participated in the questionnaire, and six out of twenty students participated in the interview. The data was analyzed by using dichotomous questions analysis. The results revealed that performance conditions and affective factors affect the students’ problems in speaking performance. The results indicate that planning was the major frequency in performance conditions, followed by support, the standard of performance, and time pressure. At the same time, self-confidence and anxiety became the major categories of affective factors and were followed by the motivation category. The writer suggests further research to investigate another factor affecting students’ problems in speaking performance with different focuses in terms of participants' scale, students’ level, and kind of speaking performance.